Menumbuhkan Kesadaran Hukum Melalui Sosialisasi Sengketa Tanah, Bangunan, dan Hak Waris di Desa Wewangrewu Kabupaten Wajo - Martono; Mustafa, Dewi Wahyuni; Sinta; Andi Apriani Putri; Putri Nur Azizah; Dini Fitria Hartanti; Muh Yusran; Ahmad Fauzan Syahbana (YP-SDI Lamaddukelleng, 2025)
This community service research aims to provide a tangible contribution to the community through a legal outreach program for the people of Wewangrewu Village, Wajo Regency. The main material for this civil law outreach program concerns land disputes and inheritance rights, considering the community's still low understanding of the legal aspects governing land ownership and inheritance. The implementation method for this activity includes interactive lectures, open discussions, and question and answer sessions with residents and village officials. The results of this activity indicate an increase in the community's legal understanding after the outreach program. Residents became more aware of the importance of legal documents such as land certificates and inheritance deeds, as well as procedures for resolving disputes through mediation or legal channels. This program is expected to be the first step in building legal awareness in the village community in a sustainable manner.